The polyproline-motif of S6K2: eIF5A translational dependence and importance for protein-protein interactions - Meneguello, Leticia [UNESP]; Barbosa, Natália M. [UNESP]; Pereira, Karina D. [UNESP]; Proença, André R. G.; Tamborlin, Leticia [UNESP]; Simabuco, Fernando M.; Iwai, Leo K.; Zanelli, Cleslei F. [UNESP]; Valentini, Sandro R. [UNESP]; Luchessi, Augusto D. [UNESP] (Wiley, 2019)
Ribosomal S6 kinase 1 (S6K1) and S6K2 proteins are effectors of the mammalian target of rapamycin complex 1 pathway, which control the process of protein synthesis in eukaryotes. S6K2 is associated with tumor progression and has a conserved C-terminus polyproline rich motif predicted to be important for S6K2 interactions. It is noteworthy that the translation of proteins containing sequential prolines has been proposed to be dependent of eukaryotic translation initiation factor 5A (eIF5A) translation factor. Therefore, we investigated the importance of polyproline-rich region of the S6K2 for its intrinsic phosphorylation activity, protein-protein interaction and eIF5A role in S6K2 translation. In HeLa cell line, replacing S6K2 polyproline by the homologous S6K1-sequence did not affect its kinase activity and the S6K2 endogenous content was maintained after eIF5A gene silencing, even after near complete depletion of eIF5A protein. Moreover, no changes in S6K2 transcript content was observed, ruling out the possibility of compensatory regulation by increasing the mRNA content. However, in the budding yeast model, we observed that S6K2 production was impaired when compared with S6K2∆Pro, after reduction of eIF5A protein content. These results suggest that although the polyproline region of S6K2 is capable of generating ribosomal stalling, the depletion of eIF5A in HeLa cells seems to be insufficient to cause an expressive decrease in the content of endogenous S6K2. Finally, coimmunoprecipitation assays revealed that the replacement of the polyproline motif of S6K2 alters its interactome and impairs its interaction with RPS6, a key modulator of ribosome activity. These results evidence the importance of S6K2 polyproline motif in the context of S6Ks function.
Keywords: eukaryotic translation initiation factor 5A; polyproline; protein interaction; ribosomal protein L7a; ribosomal protein S6; ribosomal protein S6 kinases; ribosomal S6 kinase 2